2013
DOI: 10.1016/j.immuni.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible Cholesterol-25-Hydroxylase Broadly Inhibits Viral Entry by Production of 25-Hydroxycholesterol

Abstract: SUMMARY Interferons (IFN) are essential antiviral cytokines that establish the cellular antiviral state through upregulation of hundreds of interferon-stimulated genes (ISGs), most of which have uncharacterized functions and mechanisms. We identified Cholesterol-25-hydroxylase (Ch25h) as an antiviral ISG that can convert cholesterol to a soluble antiviral factor, 25-hydroxycholesterol (25HC). Ch25h expression or 25HC treatment in cultured cells broadly inhibits enveloped viruses including VSV, HSV, HIV, and MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
665
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 557 publications
(721 citation statements)
references
References 29 publications
(33 reference statements)
26
665
0
5
Order By: Relevance
“…Although two recent independent studies demonstrated the broad antiviral activity of 25OHC, the mechanism by which 25OHC suppresses viral infection is still unclear (11,12,59). We demonstrate that 25OHC significantly alters important plasma membrane lipid species and activates the ISR, both of which may contribute to the antiviral activity of 25OHC.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 62%
See 3 more Smart Citations
“…Although two recent independent studies demonstrated the broad antiviral activity of 25OHC, the mechanism by which 25OHC suppresses viral infection is still unclear (11,12,59). We demonstrate that 25OHC significantly alters important plasma membrane lipid species and activates the ISR, both of which may contribute to the antiviral activity of 25OHC.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 62%
“…Experiments described by Liu et al (12) suggest that inhibition of viral entry is a major mechanism by which 25OHC suppresses viral infection. Our lipidomic analysis demonstrated large increases in cholesterol esters consistent with significant recycling of membrane cholesterol to the ER and decreases in sphingomyelin.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Upon recognizing viral components, host innate immune cells are activated to produce type I interferon (IFN) and proinflammatory cytokines, which are important for elimination of the invading pathogens [1,2]. In particular, the inducible production of type I IFN plays pivotal roles in antiviral immune responses because an appropriate amount of type I IFN induces cellular resistance to viral infection and triggers apoptosis of virus-infected cells [3].…”
Section: Introductionmentioning
confidence: 99%